2001
DOI: 10.1073/pnas.211280698
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from the amino terminal mdm-2-binding domain of p53, designed from conformational analysis, are selectively cytotoxic to transformed cells

Abstract: We have synthesized three peptides from the mdm-2 binding domain of human p53, residues 12-26 (PPLSQETFSDLWKLL), residues 12-20, and 17-26. To enable transport of the peptides across the cell membrane and at the same time to maximize the active mdm-2 binding ␣-helical conformation for these peptides, each was attached at its carboxyl terminus to the penetratin sequence, KKWKMRRNQF-WVKVQRG, that contains many positively charged residues that stabilize an ␣-helix when present on its carboxyl terminal end. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
93
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 23 publications
15
93
2
Order By: Relevance
“…None of these sets of cells was induced to undergo apoptosis as revealed by the absence of enhanced caspase activity above background (Fig. S2B), consistent with our prior findings that PNC-27 induces tumor cell necrosis and not apoptosis (1)(2)(3)(4)(5). Control peptide PNC-29 (200 μg∕ml), had no effect on either LDH release or the viability of any of the four sets of transfected cells, suggesting that PNC-27 binds specifically to HDM-2 on the cell membrane, allowing for its cytotoxicity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…None of these sets of cells was induced to undergo apoptosis as revealed by the absence of enhanced caspase activity above background (Fig. S2B), consistent with our prior findings that PNC-27 induces tumor cell necrosis and not apoptosis (1)(2)(3)(4)(5). Control peptide PNC-29 (200 μg∕ml), had no effect on either LDH release or the viability of any of the four sets of transfected cells, suggesting that PNC-27 binds specifically to HDM-2 on the cell membrane, allowing for its cytotoxicity.…”
Section: Resultssupporting
confidence: 91%
“…We have found previously that the peptide PNC-27, containing the HDM-2-binding domain of p53, residues 12-26, attached to a transmembrane-penetrating or membrane residency peptide (MRP) on its carboxyl terminal end, and PNC-28 (p53 residues 17-26-MRP) induce tumor cell necrosis by forming pores in cancer cell membranes but have no effects on a number of untransformed cells, including human stem cells from cord blood (1)(2)(3)(4), and eradicate tumors in nude mice (5). The p53-HDM-2 complex results in the catabolism of p53 (6).…”
Section: Hdm-2 Binding | Membranolysis | Three-dimensional Structure mentioning
confidence: 99%
“…The peptide activated the p53 system and induced apoptosis when added directly to cultured tumor cell lines. However, it has been reported that p53 C-terminusderived Mdm2-binding peptides have p53-independent cytotoxicity to transformed cells (Kanovsky et al, 2001), suggesting that under certain circumstances these peptides may act by means other than just blocking p53 degradation. There have also been efforts to identify natural products and synthetic small molecules that could impede binding of p53 and Mdm2.…”
Section: Axis Of Regulation: Diverse Signals From Multiple Pathwaysmentioning
confidence: 99%
“…We had shown previously that this p53 N-terminal peptide induced cell death only by necrosis without apoptosis. 36,37 …”
Section: Lactate Dehydrogenase Release Assay For Detection Of Necrosismentioning
confidence: 99%
“…As shown in Figure 3b, when compared to the maximal LDH release (MLR), early LDH release into the cytoplasm by 1 hr did not occur after exposure to 30 M p53p-Ant. The positive control for necrosis, 30 M p53(15)Ant that is a p53 N-terminal peptide (aa [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] shown by us to induce only necrosis without any evidence for apoptosis, 36,37 was carried out simultaneously. The N-terminal p53 peptide induced significant necrosis as evidenced by an early LDH release assay by 1 hr.…”
Section: P53 C-terminal Peptide-induced Cell Death: Apoptosis Vs Necmentioning
confidence: 99%